2018
DOI: 10.1038/s41598-018-25157-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional insights into the interplay between DNA interaction and metal coordination in ferric uptake regulators

Abstract: Ferric uptake regulators (Fur) are a family of transcription factors coupling gene regulatory events to metal concentration. Recent evidence has expanded the mechanistic repertoires employed by Fur to activate or repress gene expression in the presence or absence of regulatory metals. However, the mechanistic basis underlying this extended repertoire has remained largely unexplored. In this study, we used an extensive set of mutations to demonstrate that Campylobacter jejuni Fur (CjFur) employs the same surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…To date, three-dimensional structures have been reported for Fur proteins from P. aeruginosa (PDB ID: 1MZB) (Pohl et al, 2003), Vibrio cholerae (PDB ID: 2W57) (Sheikh and Taylor, 2009), H. pylori (PDB ID: 2XIG) (Dian et al, 2011), Campylobacter jejuni (PDB IDs: 4ETS, 6D57) (Butcher et al, 2012; Sarvan et al, 2018b), Francisella tularensis (PDB ID: 5NHK) (Pérard et al, 2018), and for a DNA-binding domain from E. coli Fur (PDB ID: 2FU4) (Pecqueur et al, 2006). A recent study showed the structure of Fur homolog from Magnetospirillum gryphiswaldense MSR-1 in a complex with manganese and E. coli Fur box (PDB ID: 4RB1) (Deng et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three-dimensional structures have been reported for Fur proteins from P. aeruginosa (PDB ID: 1MZB) (Pohl et al, 2003), Vibrio cholerae (PDB ID: 2W57) (Sheikh and Taylor, 2009), H. pylori (PDB ID: 2XIG) (Dian et al, 2011), Campylobacter jejuni (PDB IDs: 4ETS, 6D57) (Butcher et al, 2012; Sarvan et al, 2018b), Francisella tularensis (PDB ID: 5NHK) (Pérard et al, 2018), and for a DNA-binding domain from E. coli Fur (PDB ID: 2FU4) (Pecqueur et al, 2006). A recent study showed the structure of Fur homolog from Magnetospirillum gryphiswaldense MSR-1 in a complex with manganese and E. coli Fur box (PDB ID: 4RB1) (Deng et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of gene expression in bacteria usually occurs at the transcriptional level by action of DNA-binding proteins (Hantke, 2001; Lee and Helmann, 2007). Among such proteins is the ferric uptake regulator (Fur), the main representative of the Fur superfamily, which can regulate expression of genes in response to iron availability through several different mechanisms (Pecqueur et al, 2006; Lee and Helmann, 2007; Fillat, 2014; Sarvan et al, 2018a,b). Taking into account the classical hypothesis based on a canonical functional mode, under high-iron conditions Fur becomes ferreted and binds to specific Fur box sequences located in promoters of regulated genes, which results in prevention of their transcription through steric hindrance of RNA polymerase (Hantke, 2001; Deng et al, 2015; Sarvan et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite reports of both monomeric (20) and higher oligomeric (21) forms of Fur detected in solution, the physiologically relevant form of the protein is thought to be the homodimer. This is stabilized by a large buried interface between Cterminal dimerization domains (22) and, in most cases, the binding of a structural Zn 2+ (23) ion by four conserved Cys residues (24). Occupancy of this structural site (S1) is required, but not sufficient, for DNA binding.…”
Section: '-Tgataatgataatcattatca-3'mentioning
confidence: 99%
“…Various models of Fur‐DNA binding sites have been proposed, including a single 9‐1‐9 inverted repeat (Chen et al ., ), a head‐to‐head‐to‐tail 6‐mer repeat (Escolar et al ., ) and a minimal 7‐1‐7 repeat (Butcher et al ., ). Therefore, the sequence recognized by Fur seems to be a highly degenerate AT‐rich region, but the molecular mechanisms and structural basis of Fur‐DNA binding are still unclear, and its study remains under intense investigation (Deng et al ., ; Sarvan et al ., ).…”
Section: Introductionmentioning
confidence: 97%